2013
DOI: 10.1002/nav.21518
|View full text |Cite
|
Sign up to set email alerts
|

Review of the ordered and proportionate flow shop scheduling research

Abstract: Ordered flow shop models have appeared in the literature since the mid-1970s and proportionate flow shop models have appeared since the early 1980s. We provide a detailed review of these models along with some analysis and potential topics for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Using Eqs. (11,16), Eq. (13) becomes C 2 max = 2q n + p 1 + i−1 j=1 p j + P (D) = 2q n + p 1 + i−1 j=1 p j + P (C * ) + P (D) − P (C * ) = 2q n + p 1 + i−1 j=1 p j + P (C * ) + P (C * ) − P (D) ≤ 2q n + p 1 + i−1 j=1 p j + P (C * ) + P (C * ) ≤ C i max + P (C * )…”
Section: Run a (1 + )-Approximation Formentioning
confidence: 99%
See 1 more Smart Citation
“…Using Eqs. (11,16), Eq. (13) becomes C 2 max = 2q n + p 1 + i−1 j=1 p j + P (D) = 2q n + p 1 + i−1 j=1 p j + P (C * ) + P (D) − P (C * ) = 2q n + p 1 + i−1 j=1 p j + P (C * ) + P (C * ) − P (D) ≤ 2q n + p 1 + i−1 j=1 p j + P (C * ) + P (C * ) ≤ C i max + P (C * )…”
Section: Run a (1 + )-Approximation Formentioning
confidence: 99%
“…The scheduling of medical tests in an outpatient health care facility and the scheduling of classes/exams in an academic institution are two typical examples, where the patients (students, respectively) must complete a number of medical tests (academic activities, respectively); some of these activities must be done in a specified sequential order while the others can be finished in any order; and the time-spans for all these activities should not overlap with each other. The proportionate shops were also introduced in the 1980's [10] and they are one of the most specialized shops with respect to the job processing times which have received many studies [11].…”
Section: Introductionmentioning
confidence: 99%
“…We should also point out that the F m / p r p t / C max problem is a special case of the ordered flow shop F m / o r d r / C max problem introduced by Smith et al and reviewed by Panwalkar et al . Smith et al showed that the F m / o r d r / C max problem is solvable in O ( n log n ) time when each job has its shortest (longest) processing time on M 1 .…”
Section: Discussion‐conclusionmentioning
confidence: 99%
“…Numerous comprehensive reviews have been published in the field of production scheduling (Hart et al 2005;Biskup 2008;Koulamas 2010;Panwalkar et al 2013). These studies include many scheduling problems: single-machine scheduling (Koulamas 2010;, parallel machine scheduling (Vallada and Ruiz 2011;Yanga et al 2012), job shop scheduling (Weng and Ren 2006), flow shop scheduling (Panwalkar et al 2013), flexible manufacturing system scheduling (Tomastik et al 1996;, and order scheduling at the company and supply chain levels Guo et al 2013a, b).…”
Section: Previous Studies In Production Schedulingmentioning
confidence: 99%